IMPROVING STUDENT LEARNING OUTCOMES THROUGH IMAGE MEDIA THE THEME OF CONDUCT IN STUDY OF SKY OBJECTS AND NATURAL EVENTS IN CLASS I 003 STATE ELEMENTARY SCHOOL - Cicih Cicih (Indonesian Journal of Basic Education, 2021)
This study aims to improve student learning outcomes, with the research subject being the first grade students of the State Elementary School 003 Rambah, totaling 25 people. This research was carried out with research procedures consisting of planning, implementation, observation, and reflection. The results showed a pretty good increase. In the first cycle, there were 9 students whose scores were below the KKM and 16 students who had completed, in the second cycle there were no more students whose scores were below the KKM. This proves that the use of image media in science learning can improve learning outcomes.